ANALISIS KINERJA REKSA DANA SAHAM MENGGUNAKAN METODE SHARPE, M SQUARE DAN INFORMATION RATIO DENGAN INDEKS LQ-45 SEBAGAI BENCHMARK - Meinanda Dwi Cahya; Yulia Efni; Fitri Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research was aims to determine the mutual fund performance to the benchmark by using Sharpe, M Square and Information Ratio Method. The population in this research was mutual fund listed in Financial Service Authority as many as 245 mutual funds. The sample collection has been carried out by using purposive sampling technique. Based on determined criteria, the samples are 23 mutual funds. The measurement of mutual fund performance and its benchmark used Sharpe, M Square and Information Ratio Method. The analysis the data, this researh is defferent test by using Statistical Package for the Social Sciences (SPSS) version 23. The result of this research shows based on the Mann-Whitney U different test has concluded that there is no significant difference of mutual fund performance with LQ-45 Index measured by Sharpe Method. There is no significant difference of mutual fund performance with LQ-45 Index measured by M Square Method. There is no significant difference of mutual fund performance with LQ-45 Index measured by Information Ratio Method. Moreover, the result of this research shows based the Kruskal Wallis different testhas concluded that there is no significant different of mutual fund performance measured by Sharpe, M Square and Information Ratio Method.Key Word : Mutual Fund, Mutual Fund Performance, Sharpe, M Square and Information Ratio